Follow-up of renal impairment results among attendees taking HIV Pre-Exposure Prophylaxis at a Sydney Sexual Health Clinic. (June 2020) - Comninos, NB; Foster, R; Varma, R; Bourne, C
Renal monitoring is recommended for Pre-Exposure Prophylaxis (PrEP) users. We aimed to explore follow-up and outcomes among PrEP users with renal impairment (defined as estimated glomerular filtration rate <65 mL/min/1.73 m 2 ) attending Sydney Sexual Health Centre. Time to follow-up was analysed for impairment results over a 12-month period (January–December 2018); 48/2504 (1.9%) tests among 1700 attendees showed impairment. Follow-up occurred in 39/48 (81.3%) impairment results after a median of 42 days. PrEP was ceased in 3/6 cases of non-resolving/persisting impairment, with one case of subsequent human immunodeficiency virus infection. Maintaining engagement and follow-up of those with renal impairment are important aspects of PrEP service provision.